Juridical Analysis Comparison of Electronic Civil Code The Role of the Land - Frans Thiodoris; Mohammad Roesli; Adies Kadir (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
The purpose of this research is a comparative juridical analysis of buying and selling electronic commerce with the Civil Code. The research method uses a normative juridical research method, which focuses on the study starting from the provisions of the applicable laws and regulations, accompanied by legal theories and principles related to the problems studied. Research results For people to buy goods online to be more careful so that there is no fraud or deception that occurs in online buying and selling transactions. holding a registration of all activities related to the public interest in electronic traffic, including the registration of electronic businesses in the form of virtual shops or other virtual services and the obligation to register a buyer in a payment system operating company so that the transaction process can run smoothly and not neither party feels disadvantaged. For parties who do not carry out their responsibilities in accordance with the mutually agreed upon agreement, the aggrieved party may be sued civilly to obtain compensation payments as stated in Article 12 of the ITE Law.